2009
DOI: 10.1007/s11240-009-9531-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences in cell wall polysaccharide composition between embryogenic and non-embryogenic calli of Medicago arborea L.

Abstract: Analysis of cell wall polysaccharide composition of embryogenic and non-embryogenic calli obtained from hypocotyl and petiole explants from Medicago arborea L. revealed significant differences. For calli induced from both hypocotyls and petioles, levels of total sugars, pectins, and hemicelluloses were higher in embryogenic than in non-embryogenic calli. Whereas in the residual cellulose fraction, the highest levels of sugar were detected in non-embryogenic calli. When comparing the two donor sources of callus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…In the maize callus, the extracellular matrix surface network (ECMS) of the embryogenic cells contained the AGP epitope, which is recognised by the JIM4 antibody; while, the non-embryogenic callus cells were devoid of this epitope (Šamaj et al 1999, 2008). Analysis of the cell wall polysaccharide composition of the embryogenic and non-embryogenic calli that had been obtained from hypocotyl and petiole explants from Medicago arborea L. has revealed that the levels of total sugars, pectins, and hemicelluloses were higher in the embryogenic callus than in the non-embryogenic callus (Endress et al 2009). In addition, during the somatic embryogenesis of Trifolium nigrescens Viv., it was demonstrated that the low methylesterified homogalacturonan (HG), which is recognised by the JIM5 antibody, and the arabinan from side chains of rhamnogalacturonan I (RG I), which is recognised by the LM6 antibody, were detected in the embryogenic sectors of the explant (Pilarska et al 2013).…”
Section: Jim20mentioning
confidence: 99%
“…In the maize callus, the extracellular matrix surface network (ECMS) of the embryogenic cells contained the AGP epitope, which is recognised by the JIM4 antibody; while, the non-embryogenic callus cells were devoid of this epitope (Šamaj et al 1999, 2008). Analysis of the cell wall polysaccharide composition of the embryogenic and non-embryogenic calli that had been obtained from hypocotyl and petiole explants from Medicago arborea L. has revealed that the levels of total sugars, pectins, and hemicelluloses were higher in the embryogenic callus than in the non-embryogenic callus (Endress et al 2009). In addition, during the somatic embryogenesis of Trifolium nigrescens Viv., it was demonstrated that the low methylesterified homogalacturonan (HG), which is recognised by the JIM5 antibody, and the arabinan from side chains of rhamnogalacturonan I (RG I), which is recognised by the LM6 antibody, were detected in the embryogenic sectors of the explant (Pilarska et al 2013).…”
Section: Jim20mentioning
confidence: 99%
“…The use of monoclonal antibodies has shown that the distribution of different pectic epitopes in cell walls is developmentally regulated and can also be tissue, organ and species specific (Bush and McCann 1999;Willats et al 1999;McCartney et al 2000). In the embryogenic cultures of carrot (Kikuchi et al 1995) and Medicago arborea (Endress et al 2009) differences were evident in the pectic polysaccharide content between embryogenic and non-embryogenic callus cells. Data relating to the distribution of specific pectic epitopes during SE are scarce and indicate differences in the methyl-esterification of homogalacturonan (HG) during the early stages of SE (Verdeil et al 2001;Š amaj et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Pectins are the major components of the primary cell walls of all terrestrial plants (Pilarska et al, 2013). In studies with Medicago arborea (Endress et al, 2009), pectin content diff erences were observed in embryogenic and non-embryogenic callus cells. Evidence regarding the specifi c distribution of pectin epitopes during somatic embryogenesis is scarce (Pilarska et al, 2013), but embryogenic callusproliferative cells have been shown to contain large amounts of reactive pectins (Xu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%